ANALISIS KONDISI FISIK ATLET BOLA VOLI USIA 16-18 TAHUN DI KLUB JVC KOTA MALANG - M.Fibriyanto; Atiq Noviudin Pritama, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The failure in the selection held by PBVSI East Java at the U-17 level is estimated because the physical condition is still lacking to compete in the East Java level event. With the analysis of physical condition, it is hoped that it can provide an evaluation to the relevant team about the importance of good physical condition. The purpose of this study is to analyze the physical condition of volleyball athletes. This study uses a quantitative approach method using a survey method. The sample used by male volleyball athletes aged 16-18 years at the JVC club in Malang City and the subjects of this study amounted to 25 male athletes. The physical condition analysis data that was measured was arm muscle strength, abdominal muscle strength, endurance, leg muscle explosiveness, arm muscle explosiveness, agility, flexibility, coordination, and balance. The results obtained were the physical condition component of agility using the side step test and the explosive power component of leg muscles using vertical jump included in the very good category, flexibility using the standink trunk flexion test was included in the good category. arm muscle strength using the push up test, abdominal muscle strength using the sit up test and balance using the bass test are included in the sufficient category, coordination using ball wall pass is categorized as less and less once, arm muscle explosiveness using the seated medicine ball power throw test is included in the less category, endurance (Vo2max) using bleep test is included in the category of less once. This conclusion suggests that the training program needs to be focused on improving the aspects that are still weak.